Dynamic 18F-Pretomanid PET imaging in animal models of TB meningitis and human studies - Filipa Mota; Camilo A. Ruiz-Bedoya; Elizabeth W. Tucker; Daniel P. Holt; Patricia De Jesus; Martin A. Lodge; Clara Erice; Xueyi Chen; Melissa Bahr; Kelly Flavahan; John Kim; Mary Katherine Brosnan; et al. (Nature Communications, 2022)
Pretomanid has been approved for use in cases of multi-drug resistant pulmonary tuberculosis, yet the penetration of this antibiotic into other target tissues is not well established. Authors provide insight on pretomanid pharmacokinetics in the central nervous system, using positron emission tomography in animal models, and human studies.